Ketimpangan yang Dinormalisasi: Analisis Sosiologis atas Representasi Keluarga dalam Novel Dompet Ayah Sepatu Ibu - Hidayat, Novita; Aisyah, Siti; Husani, Vini Vidi; Abdurahman, Abdurahman (Lembaga Yasin AlSys, 2026)
Studies on family, poverty, and social inequality in literary works have become a focus in various previous studies. However, research that specifically discusses the normalization of inequality in the representation of family in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen remains limited. This study aims to analyze the representation of family and explain the forms of normalization of social inequality presented through the relationships, sacrifices, and life experiences of the characters. This study employed a qualitative approach with an analytical descriptive method and a sociology of literature design. The data source of this study was the novel Dompet Ayah Sepatu Ibu, while the research data consisted of narratives, dialogues, events, and symbols related to family and social inequality. Data were collected through reading and note-taking techniques and were then analyzed using qualitative content analysis. The results show that family in the novel is represented as a space of affection as well as a space in which social inequality takes place. This inequality appears through economic limitations, the sacrifices of family members, children’s responsibilities, the limited roles of parents, and education as a hope for social mobility. These findings contribute to the development of sociology of literature studies, particularly in understanding the family as a space for the reproduction of social inequality. The conclusion of the study emphasizes that inequality within the family does not always appear as open conflict, but can be normalized through habits, sacrifice, and moral demands in everyday life.